تقدير الذات وعلاقته بالدافعية للتعلم لدى تلميذ الأقسام النهائية - عبد الغني مسعودي; محمد الأمين رمه (جامعة الوادي - University of Eloued, 2025)
"تهدف الدراسة إلى الكشف على طبيعة العلاقة بين تقدير الذات والدافعية للتعلم لدى طلبة السنة النهائية من المرحلة الثانوية، حيث تمت صياغة الإشكالية العامة على النحو التالي: هل يساهم تقدير الذات في الدافعية للتعلم لدى طلبة السنة النهائية للمرحلة الثانوية. وقد شملت عينة الدراسة 100 تلميذ وتلميذة، وتم تطبيق مقياس تقدير الذات لكوبر سميث (1967)، ومقياس الدافعية للتعلم ليوسف قطامي (1989) الذي أعده اعتمادا على مقياس الدافعية للتعلم المدرسي لكل من ""كوزوكي"" و""ورسال""، واتبعنا المنهج الوصفي تم في معالجة البيانات، ثم استخدمنا كل من الانحدار الخطي المتعدد، ومعامل الارتباط بيرسون، وبعد تطبيق الأدوات المستخدمة واستخلاص النتائج، تم التوصل إلى ما يلي: - يساهم ارتفاع مستوى تقدير الذات لدى التلاميذ في ارتفاع مستوى دافعيتهم نحو التعلم. - توجد علاقة ارتباطية موجبة بين الذات العامة والدافعية للتعلم. - توجد علاقة إيجابية بين الذات الاجتماعية والدافعية. - توجد علاقة إيجابية شاملة بين تقدير الذات بجميع أبعاده والدافعية للتعلم. - توجد فروق دالة إحصائيا في تقدير الذات تعزى لمتغير الشعبة. - لا توجد فروق دالة إحصائيا في تقدير الذات تعزى لمتغيري الجنس والإعادة. " "The study aims to explore the nature of the relationship between self-esteem and motivation to learn among final-year secondary school students. The general problem was formulated as follows: Does self-esteem contribute to motivation to learn among final-year secondary school students? The study sample included 100 male and female students. The self-management scales of Coopersmith (1967) and the motivation to learn scale of Youssef Qatami (1989) were applied, based on the motivation to learn scale of Kozuki and Worsal. The data were processed using a descriptive approach, followed by multiple linear regression and Pearson's correlation coefficient. After applying the tools used and extracting the results, the following conclusions were reached: - High levels of self-esteem among students contribute to high levels of motivation to learn. - There is a positive correlation between general self-esteem and motivation to learn. - There is a positive relationship between social self-esteem and motivation. - There is a comprehensive positive relationship between self-esteem in all its dimensions and motivation to learn. - There are statistically significant differences in self-esteem attributed to the department variable. - There are no statistically significant differences in self-esteem attributed to the gender and repetition variables."
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: الدافعية للتعلم; تقدير الذات; The prefer of self; Defence to stady